Lesya Ukrainka and the Theme of Women’s Liberation in her Literary Works - Ots, Ingrid; Lankina, Liubov (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
This article examines the contribution of Lesya Ukrainka (1871–1913) to the development of feminist thought and the influence of the early 20th century Ukrainian social context on her work. Special attention is given to the theme of women’s emancipation in Ukrainka’s writings, analyzed through the lens of Alain Touraine’s social theory, which views feminism as a cultural movement aimed at deep societal transformation, including the creation of new cultural codes. The primary goal of the article is to show how Ukrainka used literature to advance feminist ideas, such as the expansion of women’s rights. Two works are analyzed: the essay New Perspectives and Old Shadows, where Ukrainka critiques Western European literature for its superficial portrayal of women, and the poetic drama The Forest Song, which challenges traditional gender roles through the characters Mavka and Lukash. Ukrainka portrays women as active agents capable of independence, thereby questioning established patriarchal norms. The authors emphasize the significance of Lesya Ukrainka’s literary legacy in the development of Ukrainian feminism, especially in its connection with the national liberation movement. The struggle for women’s autonomy in Ukraine was closely intertwined with the movement for national sovereignty, giving Ukrainian feminism distinctive characteristics that can be seen through the analysis of the work of female writers.